Systematic Literature Review on Optical Character Recognition Methods for Text Extraction - Nurcahyo, Krisna Bayu Aditya; Ricky Eka Putra; Yuni Yamasari (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The development of technology has driven a significant increase in the need for document digitization and automation of text-based data processing. A systematic review is needed to identify progress related to the development of OCR in text extraction. Therefore, this study presents a systematic literature review on the development and use of OCR in text extraction using the PRISMA method. The study began with an initial search of 38 studies, which were then selected based on established criteria. Seven relevant articles were successfully identified through a focused search using the keywords